Enhancement Of The Low Contrast Image Using Fuzzy Set Theory - Hasikin, Khairunnisa; Mat Isa, Nor Ashidi (2012)
This paper presents a fuzzy grayscale enhancement technique for low contrast image. The degradation of the low contrast image is mainly caused by the inadequate lighting during image capturing and thus eventually resulted in nonuniform illumination in the image.